2014
DOI: 10.1002/hed.23661
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant chemoradiotherapy versus altered fractionation radiotherapy in the radiotherapeutic management of locoregionally advanced head and neck squamous cell carcinoma: An adjusted indirect comparison meta-analysis

Abstract: Concomitant CRT and hyperfractionated RT are comparable to one another on indirect comparison in the radiotherapeutic management of locoregionally advanced HNSCC. Any form of acceleration (with or without total dose reduction) may not compensate fully for lack of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
3
7
0
1
Order By: Relevance
“…An adjusted indirect comparison meta-analysis has suggested that CRT is better as compared to accelerated RT (with or without total dose reduction). 12 The results of the present study are consistent with their findings. There is some evidence from MARCH, as well as the Groupe d'Oncologie Radioth erapie Tête et Cou 99-02 and RTOG 0129, that only acceleration without the addition of concurrent chemotherapy may not result in true treatment intensification.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An adjusted indirect comparison meta-analysis has suggested that CRT is better as compared to accelerated RT (with or without total dose reduction). 12 The results of the present study are consistent with their findings. There is some evidence from MARCH, as well as the Groupe d'Oncologie Radioth erapie Tête et Cou 99-02 and RTOG 0129, that only acceleration without the addition of concurrent chemotherapy may not result in true treatment intensification.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the multiple factors mentioned above. An adjusted indirect comparison meta‐analysis has suggested that CRT is better as compared to accelerated RT (with or without total dose reduction) . The results of the present study are consistent with their findings.…”
Section: Discussionsupporting
confidence: 91%
“… 36 39 A pairwise meta-analysis directly comparing the efficacy of CF_CRT with altered fractionation radiotherapy alone in locoregionally advanced head and neck squamous cell carcinoma significantly favored CF_CRT for OS (HR: 0.73, 95% CI: 0.62–0.86), DFS (HR: 0.79, 95% CI: 0.68–0.92) and LRC (HR: 0.71, 95% CI: 0.59–0.84), and there were no significant differences in the incidence of severe acute toxicity (dermatitis and mucosa). 40 However, the results of an adjusted indirect overall comparison meta-analysis suggested no significant difference between them in OS, 41 which is in accordance with our NMA results. There were no significant differences between CF_CRT and other altered fractionation radiotherapy treatments in OS and DFS.…”
Section: Discussionsupporting
confidence: 88%
“…This can be considered commensurate to the 6.5% benefit attributed to conventionally fractionated CCRT compared with similar radiotherapy alone, as shown by the updated MACH-NC metaanalysis [11]. An indirect comparison [16] from the MACH-NC and MARCH meta-analyses has also shown the equivalence of HFRT and CCRT for overall survival.…”
Section: Discussionmentioning
confidence: 88%
“…The evidence for the superiority of one approach of treatment intensification over the other remains to be established due to a relative lack of trials directly comparing the two, with the choice currently being dictated by personal and/or institutional biases. An indirect comparison meta-analysis [16] based on the MACH-NC and MARCH meta-analyses concluded that both CCRT and HFRT are significantly better than conventionally fractionated radiotherapy alone, but are comparable with one another for overall survival. It also concluded that accelerated radiotherapy (AXRT) alone with or without total dose reduction cannot compensate fully for the lack of chemotherapy.…”
Section: Introductionmentioning
confidence: 98%